ความต้องการจำเป็นในการเสริมสร้างความเป็นพลเมืองดิจิทัลของนักเรียนโรงเรียนมัธยมวัดนายโรง - กุณสิทธิ์ ไพลินรัตน์; กุโลภาส ธีรภัทร (An Online Journal of Education, 2018)
The aims of this research were 1) to study the current and desirable conditions of students’ digital citizenship at Matthayom Watnairong and 2) to study the needs analysis of students’ digital citizenship in Matthayom Watnairong School. The informants were the principal,vice-principals, and teachers with a total of 40 persons in Wat Nai Rong school. The tools used were a rating scale questionnaire and an approach feasibility assessment form. Data was analyzed using frequency, percentage, mean, standard deviation, and modified priority needs index (PNImodified).The research findings were as follows: 1) The desirable situation had a higher average than the current situation of digital citizenship enhancement of Wat Nai Rong students. 2) The result of needs the assessment in terms of the highest average of desirable situations was guided practice. The second in terms of average of desirable situations was awareness. The findings could be used for establishing guidelines to promote improved digital citizenship of students at Matthayomwatnairong School.